An Investigation of The Impact of Using Peer Review on Writing Skill Development - Sholikah, Fatma; Kusworo, Budik (International Journal on Advanced Science, Education, and Religion, 2025)
This study examines the impact of peer review on the development of writing skills among eleventh grade students at MA Raudlatul Ulum 2 Putukrejo. Using a qualitative descriptive approach, data were collected through observation, semi-structured interviews, and documentation of 15 female students selected through purposive sampling. The results of the study indicate that peer review significantly improves the quality of students' writing, particularly in terms of grammatical accuracy, vocabulary selection, idea organization, and coherence. Feedback from peers helps students identify weaknesses that were previously unrecognized, making revisions more targeted and effective. In addition to its cognitive impact, peer review also fosters metacognitive awareness, critical thinking, self-confidence, and intrinsic motivation, while also training students in the skill of providing polite and constructive feedback. This activity also reinforces the core values of the pesantren, such as cooperation, mutual assistance, and social responsibility. Teachers play a crucial role as facilitators by providing clear guidance, organizing heterogeneous groups, and ensuring the relevance of feedback. These findings indicate that peer review is a comprehensive learning strategy that integrates academic, social, and character development, making it relevant to the demands of 21st-century education, which emphasizes collaboration, communication, creativity, and critical thinking.